If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 6x + 3600 Reorder the terms: y = 3600 + 6x Solving y = 3600 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 3600 + 6x
| 13+5m=3+3m+2 | | (4x-5)*(2x^2-4x+2)= | | (4000+x*2153)*1.1=9474 | | 2x-10+3x+20+3x+10=180 | | 12a+2b=50 | | 3x-8=4x+17 | | 3x+4=3x+8 | | 1.29(20+14.99m)=75 | | (4000+x*2153)*1.1=10055 | | 18=9r+7r | | 2x-3=x-12 | | -5z-7z=35 | | 25+7x= | | 2x-8=-64 | | (5x^2+7)*(2x^3-2x+3)= | | (5x^2+7)+(2x^3-2x+3)= | | 2x+3=27-3x | | 8(2x-14)+14=4x-25 | | 8xy=zfory | | 4*2-2=5 | | 5x-13=2(x+1) | | 7y-14=22 | | 3x^2-8-10x=0 | | 6x+9=3x-3 | | 5y+1=3y+19 | | 10-5a=-4a+-18 | | 3x+-5(x+3)=8x+(-5x-9) | | 35r+7=17r-19 | | 5*2+3*2=15 | | 1+7v=-2+4v | | 15y^3-10y^2-105y= | | 2x+2-x-1=x+2 |